2022
DOI: 10.3390/cancers14051267
|View full text |Cite
|
Sign up to set email alerts
|

PITX1 Is a Regulator of TERT Expression in Prostate Cancer with Prognostic Power

Abstract: The current risk stratification in prostate cancer (PCa) is frequently insufficient to adequately predict disease development and outcome. One hallmark of cancer is telomere maintenance. For telomere maintenance, PCa cells exclusively employ telomerase, making it essential for this cancer entity. However, TERT, the catalytic protein component of the reverse transcriptase telomerase, itself does not suit as a prognostic marker for prostate cancer as it is rather low expressed. We investigated if, instead of TER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 81 publications
0
5
0
1
Order By: Relevance
“…It is assumed that it functions as a tumor-suppressor gene in several human cancer types: decreased expression level of PITX1 is observed in various malignant tumors, e.g., HNSCC [ 48 , 49 ], gastric cancer [ 50 ], lung cancer [ 51 ], and colorectal carcinoma [ 52 ]. However, there is contrary evidence that PITX1 expression is upregulated in breast cancer [ 53 , 54 ], prostate cancer [ 55 ], and lung cancer [ 56 ]. Thus, PITX1 expression is tumor-type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that it functions as a tumor-suppressor gene in several human cancer types: decreased expression level of PITX1 is observed in various malignant tumors, e.g., HNSCC [ 48 , 49 ], gastric cancer [ 50 ], lung cancer [ 51 ], and colorectal carcinoma [ 52 ]. However, there is contrary evidence that PITX1 expression is upregulated in breast cancer [ 53 , 54 ], prostate cancer [ 55 ], and lung cancer [ 56 ]. Thus, PITX1 expression is tumor-type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on PITX1 in cancer has revealed cancer-type-specific effects. While upregulation of PITX1 has been shown to be associated with tumor progression in lung adenocarcinoma 31 , kidney renal clear cell carcinoma 32 , breast 33 , epithelial ovarian 34 , and prostate 35 cancer, interestingly, in other cancer types, such as melanoma 36 , ESCC 37 , osteosarcoma 38 and head and neck squamous cell carcinoma 39 , down-regulation of PITX1 has been found to enhance tumor progression. Other EMT-related genes exclusively present in our signature included two long-non-coding RNA genes: ABHD11-AS1 and BCYRN1 .…”
Section: Discussionmentioning
confidence: 99%
“…Baena et al observed that increased TERC expression was associated with a poorer prognosis in patients with PRAD [ 16 ]. Furthermore, Poos et al found that the expression levels of PITX1, a transcription factor that regulates TERC, increased with increasing levels of Ki67 in PRAD, indicating a poorer clinical outcome [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%